Film: a strategy for the development of thinking (2010)
The present project, developed in 2009, is framed in the Pedagogical Innovations research line of the Education Masters Program of Universidad Pedagógica y Tecnológica de Colombia.The main objective was to design and apply a strategy in order to break the dogmatic image of thinking in university students, through the use of film. This action research project with a socio-critical approach, is grounded in theoretical and conceptual references concerning educational innovation, film-thinking and image-notion. Moreover, this pedagogical innovation was carried out using a pilot test as data analysis tool. It was concluded that film is a meaningful instrument for the development of thinking, given that students work with concepts and images. Critical thinking and reflection were the result of this educational innovation, which allowed students a deeper comprehension regarding the world, nature and the human being.One of the most important aspects achieved was that students were able to link real life with the fictional problems shown in the films, relationship between teacher and students also became stronger.